The tight junction protein ZO-1 is concentrated along slit diaphragms of the glomerular epithelium (The Rockefeller University Press, 1990)
The foot processes of glomerular epithelial cells of the mammalian kidney are firmly attached to one another by shallow intercellular junctions or slit diaphragms of unknown composition. We have investigated the molecular nature of these junctions using an antibody that recognizes ZO-1, a protein that is specific for the tight junction or zonula occludens. By immunoblotting the affinity purified anti-ZO-1 IgG recognizes a single 225-kD band in kidney cortex and in slit diaphragm-enriched fractions as in other tissues. When ZO-1 was localized by immunofluorescence in kidney tissue of adult rats, the protein was detected in epithelia of all segments of the nephron, but the glomerular epithelium was much more intensely stained than any other epithelium. Among tubule epithelia the signal for ZO-1 correlated with the known fibril content and physiologic tightness of the junctions, i.e., it was highest in distal and collecting tubules and lowest in the proximal tubule. By immunoelectron microscopy ZO-1 was found to be concentrated on the cytoplasmic surface of the tight junctional membrane. Within the glomerulus ZO-1 was localized predominantly in the epithelial foot processes where it was concentrated precisely at the points of insertion of the slit diaphragms into the lateral cell membrane. Its distribution appeared to be continuous along the continuous slit membrane junction. When ZO-1 was localized in differentiating glomeruli in the newborn rat kidney, it was present early in development when the apical junctional complexes between presumptive podocytes are composed of typical tight and adhering junctions. It remained associated with these junctions during the time they migrate down the lateral cell surface, disappear and are replaced by slit diaphragms. The distribution of ZO-1 and the close developmental relationship between the two junctions suggest that the slit diaphragm is a variant of the tight junction that shares with it at least one structural protein and the functional property of defining distinctive plasmalemmal domains. The glomerular epithelium is unique among renal epithelia in that ZO-1 is present, but the intercellular spaces are wide open and no fibrils are seen by freeze fracture. The presence of ZO-1 along slit membranes indicates that expression of ZO-1 alone does not lead to tight junction assembly.